(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article reviews genetic factors that influence susceptibility to various diseases, including both hereditary and multifactorial disorders. The study relies on the analysis of existing data and the results of meta-analyses to substantiate the significance of genetic predisposition in disease pathogenesis. The key results show that genetic predisposition can serve as a basis for the development of effective preventive measures and individualized treatment approaches.